Ketertarikan Peserta Didik Belajar Matematika Menggunakan LKPD dengan Model Connected Mathematics Project (CMP) - Atika Farhana; Sindi Amelia; Suripah (UNMUHBABEL PRESS, 2022)
The Covid-19 pandemic has hit the whole world, including Indonesia. This has an impact on various activities, one of which is the learning process, so the process must be done virtually. Therefore, learning alternatives are needed so that students feel interested in learning using the Connected Mathematics Project (CMP) model. This study aims to describe the learning interest of students using LKPD with the CMP model during the Covid-19 pandemic. This research is a descriptive qualitative research. The subjects of this study were students of junior high school class VIII  as many as 22 students who were randomly selected in one school. The instrument used in this study was  a learning interest questionnaire  which was distributed via distributed google form which contained 19 questions as a reference to determine studentâ€™s learning interest using the LKPD with the CMP model. The data analysis technique used is qualitative analysis. The results of the study showed that there was a positive impact on students' learning interest, seen from the average percentage of the indicator was 80.09% with a good category. Then for each indicator there are two indicators with very good categories, and four indicators with good criteria. Based on the results of this study, it can be concluded that students have a good interest in learning using LKPD with the CMP model.